1996
DOI: 10.1111/j.1745-459x.1996.tb00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Flavor Compounds Affecting Consumer Acceptability of Kiwifruit

Abstract: Sensory research on kiwifruit has shown that specific sugars and acids, and volatile flavor compounds have causative effects on “sweet” and “acid” aroma and flavor attributes. New Zealand consumers (n = 162) assessed the perceived flavor intensity and acceptability of three volatile flavor compounds (ethyl butanoate, E‐2‐hexenal and hexanal) at varying levels in a model base solution. Increasing levels of ethyl butanoate positively affected all the acceptability attributes (“overall liking,”“liking of aroma,”“… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…In particular, more hydrophilic compounds were retained and more hydrophobic compounds released as sucrose concentrations increased. Research using aqueous solutions modelled on kiwifruit demonstrated that some volatiles are important in consumer liking of kiwifruit (Ball, Murray, Young, & Gilbert, 1998;Gilbert, Young, Ball, & Murray, 1996;Young, Stec, Paterson, McMath, & Ball, 1995). Three volatile compounds affected perception of sweetness (methyl benzoate, ethyl butanoate and hexanal), while (E)-2-hexenal, hexanal and ethyl butanoate increased perception of kiwifruit flavour.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, more hydrophilic compounds were retained and more hydrophobic compounds released as sucrose concentrations increased. Research using aqueous solutions modelled on kiwifruit demonstrated that some volatiles are important in consumer liking of kiwifruit (Ball, Murray, Young, & Gilbert, 1998;Gilbert, Young, Ball, & Murray, 1996;Young, Stec, Paterson, McMath, & Ball, 1995). Three volatile compounds affected perception of sweetness (methyl benzoate, ethyl butanoate and hexanal), while (E)-2-hexenal, hexanal and ethyl butanoate increased perception of kiwifruit flavour.…”
Section: Introductionmentioning
confidence: 98%
“…Studies on the causal effects of selected flavour volatiles on the intensity of sensory attributes in 'Hayward' showed that ethyl butanoate, methyl benzoate and hexanal had positive correlations with sweet aroma and flavour (McMath et al 1991;. The most pronounced effect on 'kiwifruit aroma and flavour' was produced by ethyl butanoate (Gilbert et al 1996). Paterson et al (1991 reported that ethyl butanoate, the major ester present in 'Hayward', appeared to be a predictor of flavour acceptability.…”
Section: 'Flavour Impact' Volatiles Of a Chinensis Fruitmentioning
confidence: 93%
“…Our results also showed that ethyl butanoate was the major ester present in these A. chinensis fruit. However, high concentrations of this volatile can also contribute to a 'very ripe kiwifruit-like' perception of flavour (Paterson et al 1991;Gilbert et al 1996), which is not a desirable attribute (Stec et al 1989). Thus, the balance of this volatile with others may be a more important characteristic.…”
Section: 'Flavour Impact' Volatiles Of a Chinensis Fruitmentioning
confidence: 98%
See 1 more Smart Citation
“…The characteristic "kiwifruit" flavor seems to be associated mainly with ethyl butanoate, (E)-2-hexenal and some C6 alcohols (Gilbert et al 1996;Jordán et al 2002). The fruit of A. arguta, with their very distinct aroma notes, likewise produced complex mixtures of volatiles, particularly esters which have sweet "fruity" odors (Matich et al 2003).…”
Section: Ripening Indicatorsmentioning
confidence: 99%